Fermentation as a Promising Tool to Valorize Rice-Milling Waste into Bio-Products Active against Root-Rot-Associated Pathogens for Improved Horticultural Plant Growth - Ruta Vaitkeviciene; Natalija Burbulis; Ramune Masiene; Renata Zvirdauskiene; Valdas Jakstas; Jonas Damasius; Daiva Zadeike (Fermentation, 2022)
In this study, water extracts from fermented (F), ultrasonicated (US), and enzyme-hydrolyzed (E) rice bran (RB) were evaluated against sixteen fungal plant stem and root-rot-associated pathogens. The effects of pre-treated RB additives on plant growth substrate (PGS) on bean and tomato seed germination, stem height and root length of seedlings, and chlorophyll concentration in plants were analyzed. The results showed that US-assisted pre-treatments did not affect protein content in RB, while 36 h semi-solid fermentation (SSF) reduced protein content by 10.3–14.8%. US initiated a 2.9- and 2-fold increase in total sugar and total phenolics (TPC) contents compared to the untreated RB (3.89 g/100 g dw and 0.61 mg GAE/g dw, respectively). Lactic acid (19.66–23.42 g/100 g dw), acetic acid (10.54–14.24 g/100g dw), propionic acid (0.40–1.72 g/100 g dw), phenolic compounds (0.82–1.04 mg GAE/g dw), among which phenolic acids, such as p-coumaric, cinnamic, sinapic, vanillic, and ferulic, were detected in the fermented RB. The RBF extracts showed the greatest growth-inhibition effect against soil-born plant pathogens, such as Fusarium, Pythium, Sclerotinia, Aspergillus, Pseudomonas, and Verticillium. Beans and tomatoes grown in RBUS+E- and RBF-supplemented PGS increased the germination rate (14–75%), root length (21–44%), and stem height (25–47%) compared to seedlings grown in PGS. The RB additives increased up to 44.6–48.8% of the chlorophyll content in both plants grown under greenhouse conditions. The results indicate that the biological potential of rice-milling waste as a plant-growth-promoting substrate component can be enhanced using solid-state fermentation with antimicrobial LABs and US processing.